Ecological risk assessment of sediment management areas : application to Sado Estuary, Portugal - Caeiro, Sandra (2009)
The purpose of this work was to integrate different methodologies to assess the potential ecological risk of estuarine sedimentary management areas, using the Sado Estuary in Portugal as case study. To evaluate the environmental risk of sediment contamination, an integrative and innovative approach was used involving assessment of sediment chemistry, sediment toxicity, benthic community structure, human driving forces and pressures and management areas organic load levels. The basis for decisionmaking for overall assessment was a statistical multivariate analysis appended into a score matrix tables, using a best expert judgment. The integrated approach allowed to identify from the 19 management areas analyzed, three with no risk but other three with high risk to cause adverse effects in the biota, related with the contaminants analyzed. The methodologies used showed to be effective as a support for decision making leading to future estuarine management recommendations.